Totemism in the Arabian Peninsula before Islam - brahim, lahcene (The Algerian Historical Journal, 2026)
This research aims to know the ancient Arab beliefs in the Arabian Peninsula, and their manifestations in Arab religious and social life, and to know their symbols and connotations. It also highlights the ancient Arab sanctities, especially “Totemism” that appeared among the ancient Arabs and was considered sacred with a high degree of worship, as the aspect explains. Predominant religious and social belief. Among the results reached is that the ancient Arabs believed in Totemism and defended it. They sanctified animals, plants, trees, and inanimate objects. They also believed that Totemism brought them good and warded off evil. They also forbade the people of the totem to marry each other.